Comparison of the Criteria for the Validity of Hadith in the View of the Khawarij and Sunni - Muhid, Muhid; Syabrowi, Syabrowi; Nurita, Andris (Turast: Jurnal Penelitian dan Pengabdian, 2023)
This article tries to identify the ideas of the Khawarij and Sunni in the criteria for the validity of hadith. So far, hawarij is known as a group in which there are people who left the ranks of 'Ali ibn Abu Talib after the tahkim (arbitration) incident.dTheir understanding of religion tends to be textual both in interpreting verses or understanding the Prophet's hadith. In its development, they helped formulate the criteria for the validity of the hadith as the Sunnis. Through this study the author tries to analyze how the differences and similarities in the concept of authenticity of hadith according to the Khawarij and Sunnis. In addition to aiming to enrich scientific treasures in the field of hadith science, this study also aims to explore further whether the concept coined by the Khawarij in measuring the validity of the hadith contains controversy or not when compared to the concept of the Sunnis. This methode of research is a qualitative research that is descriptive analysis. Sources of data in the form of previous studies or references in the form of books and books which contain related discussions. This study shows that in general the criteria for the validity of hadith according to the Khawarij are the same as the criteria for the validity of hadith according to the Sunnis.. They are also inconsistent in accepting the hadith.